2003
DOI: 10.1302/0301-620x.85b6.13806
|View full text |Cite
|
Sign up to set email alerts
|

Femoral impaction grafting with cement in revision total hip replacement

Abstract: e report the results of cancellous femoral impaction grafting with cement in revision hip arthroplasty in all patients from one centre who had undergone surgery more than five years previously. A total of 32 surgeons undertook femoral impaction grafting in 207 patients (226 hips). There were no deaths attributable to the revision surgery; 33 patients with 35 functioning hips died with less than five years' follow-up. One patient was lost to follow-up. Two hips (1%) developed early postoperative infection. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
140
1
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(159 citation statements)
references
References 55 publications
9
140
1
8
Order By: Relevance
“…The treatment has been described using extensively coated femoral stems [3,13,26], modular stems with distal tapers [10,12,14,15,17,19,22], and impaction bone grafting with cemented polished stems [4,7,16,21,23,25,27]. Femoral impaction grafting, first reported by Gie et al in 1993 [5], has the advantage of adding bone to the deficient femur, but it is a time-consuming procedure with reported risks of fracture ranging from 5% to 12% [1,5,7,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment has been described using extensively coated femoral stems [3,13,26], modular stems with distal tapers [10,12,14,15,17,19,22], and impaction bone grafting with cemented polished stems [4,7,16,21,23,25,27]. Femoral impaction grafting, first reported by Gie et al in 1993 [5], has the advantage of adding bone to the deficient femur, but it is a time-consuming procedure with reported risks of fracture ranging from 5% to 12% [1,5,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported high survival (77%-100%) at 5 to 19 years for femoral bone impaction grafting [4,7,16,21,23,25,27]. Halliday et al [7], reporting findings of the developers of the technique, found a survivorship of 90.5% at 11 years for femoral reoperation and 99.1% at 11 years for femoral revision for aseptic loosening as the end point. In a retrospective study of 79 patients (81 hips) followed 5 to 17 years, Garcia-Cimbrelo et al [4] found a survival rate for reoperation for any cause of 98.6%.…”
Section: Introductionmentioning
confidence: 99%
“…We have been using metal meshes to reconstruct femoral deficiencies since 1990. Because of favorable outcomes in the literature [15,20,25,39] as well as in our patients [4] and laboratory tests [18], we extended the indication of these devices to reconstruct complete circumferential proximal cortical bone loss. However, this circumferential bone loss has been considered a contraindication for the impaction bone grafting technique in the femur by one group [39].…”
Section: Introductionmentioning
confidence: 94%
“…Recently, high survivorship has been reported in three studies. Halliday et al [12] reported a survivorship rate of 99.1% at 10 to 11 years and Schreurs et al [19] reported a survivorship rate of 100% at 8 to 13 years using the Exeter TM stem (Stryker Howmedica, Newbury, UK). Mahoney et al [16] reported a survivorship rate of 97% at 4.7 years.…”
Section: Introductionmentioning
confidence: 99%